Exchange Rate Pass-through in Central and Eastern European Member States - John Beirne; Martin Bijsterbosch (European Central Bank (ECB), 2009)
This paper provides estimates of the exchange rate pass-through (ERPT) to consumer prices for nine central and eastern European EU Member States. Using a five-variate cointegrated VAR (vector autoregression) for each country and impulse responses derived from the VECM (vector error correction model), we show that ERPT to consumer prices averages about 0.6 using the cointegrated VAR and 0.5 using the impulse responses. We also find that the ERPT seems to be higher for countries that have adopted some form of fixed exchange rate regime. These results are robust to alternative normalisation of the VAR and alternative ordering of the impulse responses.
Keywords: E31; F31; 330; central and eastern Europe; Exchange Rate Pass-Through; inflation; Exchange Rate Pass-Through; Verbraucherpreisindex; VAR-Modell; Osteuropa